Effects of Olympic Combat Sports on Health-Related Quality of Life in Middle-Aged and Older People: A Systematic Review - Valdés-Badilla, Pablo; Herrera-Valenzuela, Tomás; Guzmán-Muñoz, Eduardo; Delgado-Floody, Pedro; Núñez-Espinosa, Cristian; Monsalves-Álvarez, Matias; Andrade, David Cristóbal (Frontiers in Psychology, 2022)
Olympic combat sports are unconventional physical activity strategies to train middle-aged and older people with and without health problems. This systematic review aimed to assess the available body of published peer-reviewed articles related to the effects of Olympic combat sports interventions (boxing, fencing, judo, karate, taekwondo, wrestling) on health-related quality of life in adults aged 45 and older. The search was carried out in five generic databases until July 2021 and the protocol was registered in PROSPERO (code: CRD42021244161). The PRISMA guidelines were followed and the Downs and Black checklist was used to assessed the methodological quality of the studies. After reviewing 1,151 records, only seven studies met the inclusion criteria, adding 212 participants (43.4% female) with a mean age of 63.7 years. Six studies (two with middle-aged participants and four with older people) provided data to calculate the effect size (ES) in the Olympic combat sports groups (No research that used taekwondo or wrestling as an intervention modality was found). Three studies reported beneficial changes with a small ES for the total score (d <0.40) of the health-related quality of life. Two studies reported a beneficial change with a small ES (d =0.49) and strong ES (d =4.45) for physical health. One study reported improvements with a small ES for emotional (d =0.23) and functional (d =0.26) well-being. In conclusion, interventions based on Olympic combat sports produce beneficial effects with a small and moderate ES on health-related quality of life in male and female aged 45 and older who are healthy participants, participants with Parkinson's disease, and participants with breast cancer.